LATE-ONSET POST-TRAUMATIC SUBCLAVIAN VEIN INJURY ACCOMPANYING FIRST RIB FRACTURE : A CASE REPORT - YOKONO Yoshinori; HIROSE Tomoya; OGAWA Yoshihito; OOI Kazuya; TOGAMI Yuki; NOMA Takashi; YAMADA Tomoki; NAKAE Haruhiko; MIZUSHIMA Yasuaki (Journal of the Japanese Association for the Surgery of Trauma, 2020)
A 42-year-old woman injured in a traffic accident was transferred to our hospital. Computed tomography (CT) demonstrated multiple rib fractures, including the right first rib, right hemopneumothorax, and spleen and left kidney injury. On hospital day 2, she developed circulatory collapse and cardiac arrest. Cardiopulmonary resuscitation resulted in return of spontaneous circulation. Contrast CT revealed massive right hemothorax and extravasation from a right subclavian vein (SCV) varicosity. To control the massive hemorrhage, we exposed and removed the right clavicle diaphysis, which enabled us to access the SCV and obtain hemostasis. She was discharged on hospital day 60 with no neurological deficit and full range of motion of her shoulder. Supraclavicular incision and resection of the clavicle diaphysis may be a useful method to expose an injured SCV to obtain hemostasis. 42歳女性, 交通事故により受傷された. 来院時, 見当識障害, 頻脈と酸素化不良を認め, CT検査で右第一肋骨骨折を含む両側多発肋骨骨折, 右血気胸を認めた. 第2病日に急激な循環虚脱から心停止に陥ったが蘇生により自己心拍再開を得た. 造影CT検査で右大量血胸と胸郭出口部で右鎖骨下静脈の静脈瘤と同部位からの活動性出血を認め, 緊急止血術を行った. 右鎖骨上切開を行い, 鎖骨骨幹部を除去することで鎖骨下静脈と外頸静脈の分岐部が出血源と視認でき結紮止血が可能となった. 第60病日に神経学的後遺症や右肩関節可動域制限なく転院となった. 鎖骨上切開で鎖骨を除去することは鎖骨下静脈損傷に対し良好なアプローチ方法の一つである.